Investigating the driving performance of drivers with and without autism spectrum disorders under complex driving conditions - Chee, D.; Lee, Hoe; Patomella, A.; Falkmer, Torbjorn (Informa Healthcare, 2017)
Purpose: The aim of this study was to investigate the driving performance of drivers with autism spectrum disorders under complex driving conditions. Method: Seventeen drivers with autism spectrum disorders and 18 typically developed drivers participated in a driving simulator trial. Prior to the assessment, participants completed the Driving Behaviour Questionnaire and measurements of cognitive and visual-motor ability. The driving simulation involved driving in an urban area with dense traffic and unpredictable events. Results: In comparison with the typically developed group, drivers with autism spectrum disorders reported significantly more lapses in driving, committed more mistakes on the driving simulator, and were slower to react in challenging situations, such as driving through intersections with abrupt changes in traffic lights. However, they were also less likely to tailgate other vehicles, as measured by time-to-collision between vehicles, on the driving simulator. Conclusions: The performances of licensed drivers with autism spectrum disorders appeared to be safer in respect to car-following distance but were poorer in their response to challenging traffic situations. Driver education for individuals with autism spectrum disorders should focus on quick identification of hazards, prompt execution of responses, and effective allocation of attention to reduce lapses in driving.Implications for rehabilitationDrivers with autism spectrum disorders reported significantly more lapses during driving.Drivers with autism spectrum disorders were observed to be poorer in traffic scenarios requiring critical response.Driver education for individuals with autism spectrum disorders should focus on managing anxiety and effective attention allocation while driving.Driving simulators can be used as a safe means for training critical response to challenging traffic scenarios.